Financial literacy and behavior in student financial planning action: the role of SECI strategy - Adilah A. Wahab; Wan Marhaini Wan Ahmad; Aimi Syahirah Abu Hashim; Mas Nordiana Rusli (Penerbit Universiti Kebangsaan Malaysia, 2024)
Research on the relationship between financial literacy, financial behavior, and financial planning actions (FPAs) in Malaysia is limited, with existing studies focusing mainly on financial well-being. This gap is concerning given the rising trend of bankruptcy and debt issues among young Malaysian employees. Understanding how financial literacy and behavior impact FPAs is crucial, particularly for individuals transitioning from academic to professional financial responsibilities. This paper examines these relationships among 1,105 undergraduate students in Malaysia. Using Ordinary Least Squares (OLS) regression, the study finds significant positive relationships between financial literacy, financial behavior, and FPAs, consistent with human capital and reasoned action theories. Additionally, it explores the moderating role of Socialization, Externalization, Combination, and Internalization (SECI) strategies. The results highlight that parental guidance, personal finance websites, and college information effectively moderate the relationship between financial literacy, financial behavior, and FPAs. Financial workshops also significantly moderate the relationship between financial behavior and FPAs. Overall, the findings demonstrate that both financial literacy and behavior are critical factors influencing FPAs among undergraduate students, emphasizing the need for effective financial education and support.